Foreword - O’Hara, M (Policy Press, 2020)
Shame is how they get away with it. Shame is the weapon they use. Shame is the weapon you use on yourself that makes you feel so useless. And those who are shamed most often and most deeply, made to feel ashamed for so much of their life, are the poorest among us. When others say that they are disappointed in you, they are trying to inflict shame on you. They are attempting to make you contrite and silent. To force shame upon you. The poor are the most common targets of shaming because the rich are not ashamed of...